Conidial Morphogenesis and Septin-Mediated Plant Infection Require Smo1, a Ras GTPase-Activating Protein in Magnaporthe oryzae. Issue 1 (16th November 2018) - Kershaw, Michael J; Basiewicz, Magdalena; Soanes, Darren M; Yan, Xia; Ryder, Lauren S; Csukai, Michael; Oses-Ruiz, Miriam; Valent, Barbara; Talbot, Nicholas J
Abstract: The pathogenic life cycle of the rice blast fungus Magnaporthe oryzae involves a series of morphogenetic changes, essential for its ability to cause disease. The smo mutation was identified > 25 years ago, and affects the shape and development of diverse cell types in M. oryzae, including conidia, appressoria, and asci. All attempts to clone the SMO1 gene by map-based cloning or complementation have failed over many years. Here, we report the identification of SMO1 by a combination of bulk segregant analysis and comparative genome analysis. SMO1 encodes a GTPase-activating protein, which regulates Ras signaling during infection-related development. Targeted deletion of SMO1 results in abnormal, nonadherent conidia, impaired in their production of spore tip mucilage. Smo1 mutants also develop smaller appressoria, with a severely reduced capacity to infect rice plants. SMO1 is necessary for the organization of microtubules and for septin-dependent remodeling of the F-actin cytoskeleton at the appressorium pore. Smo1 physically interacts with components of the Ras2 signaling complex, and a range of other signaling and cytoskeletal components, including the four core septins. SMO1 is therefore necessary for the regulation of RAS activation required for conidial morphogenesis and septin-mediated plant infection.